"We Are the Invasive Species": Democratizing Knowledge and Pedagogical Design as Acts of Resistance in the Public Classroom - Gal, Adiv (Journal of Ecohumanism, 2026)
This essay challenges the hierarchical and disciplinary structures of traditional science education through a critical reflection on a pedagogical sequence conducted in a public elementary school in Israel. At the center of the discussion stands a fifth-grade student’s insight, "We are the biggest invasive species", which represents a rupture from the mandated scientific narrative and a crack in the classroom power arrangement. The essay argues that the shift from a "pedagogy of transmission" to the design of learning environments that invite uncertainty, intergenerational dialogue, and activism is not merely a didactic improvement, but a political act that undermines institutional standardization. Through an analysis of practices such as "mock trials," community hackathons, citizen science, and AI-based digital creation, a model of "scientific citizenship" is presented that restores students’ agency and builds an environmental identity sustained decades after the experience.